Developmental Coordination Disorder and Joint Hypermobility in Childhood: A Narrative Review - Domenico M. Romeo; Ilaria Venezia; Margherita De Biase; Federica Ascione; Maria Rosaria Lala; Valentina Arcangeli; Eugenio Mercuri; Claudia Brogna (MDPI AG, 2022)
Children with developmental coordination disorder (DCD) and joint hypermobility could present an overlap of symptoms and motor functional difficulties. The link between these two clinical conditions has not yet been clarified. Recent studies reported a high incidence (30-50%) of motor delay in children who are referred to hypermobility and of enhanced joint hypermobility in children with DCD. The aim of this study was to provide a critical review of the literature outlining the association between DCD or limited motor performance and joint hypermobility. Studies were eligible for inclusion if they were written in English and human-based. All the studies were first selected, looking for the presence of a clinical association between developmental coordination disorder or motor performance and hyperlaxity and reporting details of outcome. After a review of the full texts, 16 articles for a total of 1898 children met the inclusion criteria. In general, there was evidence of a higher incidence of motor delay or DCD in children who are referred to hypermobility and of enhanced joint hypermobility in children with DCD with similar range of functional difficulties. These results could influence the way to support children with rehabilitation and the type of intervention according to the prevalence of one of the two conditions.